Analyzing the value of an educational program for psoriasis patients: a prospective controlled pilot study - Corinna Bubak; Marthe-Lisa Schaarschmidt; Lisa Schöben; Wiebke Katharina Peitsch; Astrid Schmieder (BMC, 2019)
Abstract Background Psoriasis is a chronic inflammatory skin disease associated with a reduced life-quality. Severe disease forms put the patients at risk for life-treating cardiovascular events, metabolic, and other immune-mediated disorders. Psoriasis patients are often not sufficiently informed about their condition leading to suboptimal treatment adherence and, consequently, worse patient outcome. We investigated the value of an educational program on knowledge and self-expertise about the disease in psoriasis patients in general and dependent on age and disease duration. Methods Regular visit psoriasis-patients were asked to participate and choose to receive an additional educational program or not. Participating patients (n = 53) filled out two questionnaires: one at study inclusion and one at the next regular visit or after the absolved educational program. Surveys included disease knowledge assessment and numeric rating scales (0-10) for self-expertise about the disease, therapy adherence, and therapy satisfaction. The Dermatology Life Quality Index (DLQI) was used to investigate the quality of life. All continuous parameters were examined for statistically significant differences by paired t-test or unpaired t-test. Continuous parameters without Gaussian distribution were analyzed with the Wilcoxon matched pairs test or the Mann-Whitney test. For all categorical parameters, Fisher's exact test was used. Results Patients who chose to be educated (n = 24) showed a significant increase in knowledge, self-expertise about the disease and amelioration of general health. No positive short-term effects were seen on the quality of life and therapy adherence. Analyzing the effect of age and disease duration, the educational program led to significant improvement of the emotional well-being in older patients (≥50 years) and with a longer disease duration as well as significant amelioration of the self-expertise about psoriasis in younger patients (< 50 years). Conclusions Patients who chose to participate in an educational program show a higher gain in knowledge and self-expertise about the psoriatic disease. Educational program thus might have a positive effect on the long-term management of psoriasis. Further long-term studies are needed to provide evidence for the influence educational programs have on outcome, quality of life, and treatment adherence of psoriatic patients. Trial registration Deutsches Register Klinischer Studien DRKS00017318 (09.10.2019), retrospectively registered.